PERGARUH_PENGOPERASIAN_FILTER_AKTIF_BERBASIS _KONTROL_PID _TERHADAP_KAPASITAS KERJA TRANSFORMATOR DISTRIBUSI DI GEDUNG_ STUDENT_CENTER_UNIVERSITAS_UDAYANA - Agung Pribadi, Satriyo; Suartika, I_M.; Janardana, I_G_N. (Jurnal SPEKTRUM; Vol 8 No 4 (2021): Jurnal SPEKTRUM, 2022)
The transformer is one of the equipmen for distributing electrical_energy from_medium voltage 20 kV to low voltage 380/220 V. Disturbance in the transformer_can_cause_Losses so that it can disrupt the flow of electric power to consumers. Harmonics_are disturbances caused by the operation of non-linear loads. This study aims to determine the effect of THDi on power Losses and working capacity of transformers at Udayana University Student Center Building with harmonics in the R phase of 10.91%, the S phase of 11.38%, and_the T phase of 17.91%. The method used is to perform simulations and analysis_with_the_results_of_harmonic measurements in Existing conditions, using an active filter, and an active PID-based filter using the Matlab application. Very optimal results were obtained using a PID-based active_filter with the results of R = 0.31%, S = 0.30%,_T = 0.35%,_and the decrease in the working_capacity_of_the_transformer_decreased_to 1%,_according _to_the_ideal_value.